Conceptual GeoHealth Framework for Disaster Response Research: Case Study for Wildland Urban Interface (WUI) Fires and Data Integration - J. Barkoski; A. Liu; E. Van Fleet; S. Ramsey; A. Miller (GeoHealth)
Abstract With climate change contributing to an increase in frequency and severity of extreme weather events like wildfires, droughts, and hurricanes, there is a growing need for coordinated research efforts to understand the impact of these events on human health. Specialized research frameworks can help interdisciplinary teams organize and visualize complex exposure‐health pathways, identify knowledge gaps, and enhance coordination and communication across diverse groups of stakeholders. This article describes the development and application of a conceptual framework for wildfire‐related exposures and human health outcomes. This framework serves as a tool for integrating data resources and mapping known and hypothesized connections, between complex wildfire exposures and human health outcomes, across the lifecycle of a wildland urban interface (WUI) fire. We also demonstrate the utility and flexibility of this framework for disaster research settings through two example applications. The first demonstrates an application for studying WUI fires and respiratory health outcomes, and the second example shows how the framework can be expanded to visualize exposure and health modeling with potential biomarkers of exposure and effect. Our GeoHealth Framework for WUI Fires illustrates complex linkages between wildfire related exposures and health outcomes and highlights areas for future study. Given the destruction and complexity of WUI fires, this framework provides an important resource that can assist with evaluating these complex exposure‐health relationships, guiding and coordinating data collection, and informing communities and decision‐makers to improve response, recovery, and future preparedness for such events in the United States and globally.